RELEVANCE AND ROLE OF RISK FACTORS IN THE DEVELOPMENT OF MYOCARDIAL INFARCTION - Андрей Георгиевич Петров; Николай Владимирович Абрамов; Сергей Николаевич Филимонов; Виктор Андреевич Семенихин (Медицина в Кузбассе)
The review is devoted to the role of risk factors in the development of myocardial infarction. Risk factor profiles and their combinations are different among patients with acute myocardial infarction (AMI). The relevance of studying risk factors for improving the prevention of myocardial infarction among the population is shown.